Lymphoepithelioma-Like Carcinoma of the Skin Treated with Wide Local Excision and Chemoradiation Therapy: A Case Report and Review of the Literature - Theresa M. Gille; Edward F. Miles; Allen O. Mitchell (Case Reports in Oncological Medicine)
Lymphoepithelioma-like carcinoma of the skin (LELCS) is a rare cutaneous neoplasm microscopically similar to undifferentiated nasopharyngeal carcinoma. It is typically nonaggressive and is treated with wide local excision. However, we present a case of a patient with a regional recurrence and more aggressive LELCS with perineural invasion and positive margins for which he was treated with wide local excision followed by chemoradiation. We discuss the use of chemoradiation for this patient and review the literature, specifically pertaining to treatment of more aggressive cases of LELCS.